Advances in the Treatment of Epilepsy by Electrostimulation of the Pulvinar - Bingyang Shan; Yang Dai; Quanlei Liu; Changkai Hou; Yihe Wang; Penghu Wei; Guoguang Zhao (Journal of Integrative Neuroscience)
Neuroregulatory therapy, encompassing deep brain stimulation and responsive neurostimulation, is increasingly gaining attention for the treatment of drug-resistant temporal and occipital lobe epilepsy. Beyond the approved anterior nucleus of the thalamus, the pulvinar nucleus of the thalamus is a potential stimulation target. Through a confluence of animal studies, electrophysiological research, and imaging studies, the pulvinar has been identified as having extensive connections with the visual cortex, prefrontal cortex, limbic regions, and multimodal sensory associative areas, playing a pivotal role in multisensory integration and serving as a propagation node in both generalized and focal epilepsy. This review synthesizes recent research on the pulvinar in relation to cortical and epileptic networks, as well as the efficacy of neuroregulatory therapy targeting the pulvinar in the treatment of temporal and occipital lobe epilepsy. Further research is warranted to elucidate the differential therapeutic effects of stimulating various subregions of the pulvinar and the specific mechanisms underlying the treatment of epilepsy through pulvinar stimulation.